PERANCANGAN STRUKTUR BETON BERTULANG KANTOR SEWA 6 LANTAI JALAN AHMAD YANI KOTA PONTIANAK: PERANCANGAN STRUKTUR BETON BERTULANG KANTOR SEWA 6 LANTAI JALAN AHMAD YANI KOTA PONTIANAK - Sudoko, Jihan; Supardi, iwan; Sasongko, Hartanto Wahyu; Muliati, Erni Puji (Jurusan Teknik Sipil Polnep, 2023)
This rental office building is designed to be built on Road Ahmad Yani, Pontianak City. Thei buildingi structure is designed usingi the Speciali Moment Resistant Framei Structure systemi (SPRMK) based on SNIi 03-2487-2013 (Requirementsi for Structurali Concretei fori Buildings). Analysis ofi earthquakei loads usingi the spectrum design methodi based on SNIi 1726-2019i (Earthquakei Resistance Planningi Proceduresi for Buildingi and Non-Buildingi Structures) for the locationi of earthquake accelerationi using the cityi ofi Tarakan. iPPPURG 2847-1989 (Guidelines for Loading Planning for Houses and Buildings) and PPPURG 1987 (Guidelines for Loading Planning for Housesi and Buildings) fori loading. In thei analysis, thei loading systemi that will be imposedi on the building isi a vertical loadingi systemi in the formi of dead andi livei loads and horizontal loads in thei form ofi earthquakei loads and structurali analysisi assistedi by computeri programmers. From the structurali analysis, it can be concludedi that the dimensionsi of the crossi section andi reinforcementi are obtained.